Business Competence, Organizational Learning and Economic Growth: Establishing the Smith-Schumpeter-Wicksell (SSW) Connection - Gunnar Eliasson (The Research Institute of Industrial Economics (IUI), 1990)
The firm is defined in terms of its financial objectives, achieved through human-based organizational competence, conferring scale economies on all other factors. Competence is developed through organizational learning, jointly produced with the value added of the firm, largely manifesting itself in organizational change. Such learning draws considerable resources, partly through mistakes and is subjected to strongly diminishing returns.
Keywords: L22; O40; 330; Organizational change; Economic growth